Epithelioid hemangioendothelioma involving the superficial femoral artery and femoral vein - Rachad Wehbe, MD; Xi Wang, BMed; Karina A. Newhall, MD, MS; Michael C. Stoner, MD; Doran S. Mix, MD; Grayson S. Pitcher, MD (Journal of Vascular Surgery Cases and Innovative Techniques)
Epithelioid hemangioendothelioma (EHE) is a rare vascular tumor. We present the case of a 64-year-old woman who presented with new-onset claudication and an atypical vascular mass involving the superficial femoral artery and femoral vein. En bloc resection and vascular reconstruction was performed which revealed a G1 EHE involving the walls of the superficial femoral artery and femoral vein with tumor cells positive for ERG-, CD31, and CAMTA-1. We discuss the preoperative workup for atypical vascular masses and the challenges associated with EHE.